Effectiveness of Reproductive Health Education Through Video Learning Multimedia on Changes in Attitudes About Prevention of Student Sexual Harassment - Nurbaya, Nurbaya (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: The study aims to determine the effectiveness of reproductive health education through Virtual Learning Media (VLM) on changes in early adolescent attitudes to prevent sexual harassment. Research Design and Methodology: The research was conducted at the Nurul Fikri Integrated Islamic Elementary School, Makassar City, using quantitative research methods with a quasi-experimental approach. The study involved 50 students from SDIT Nurul Fikri. Findings and Discussion: The results indicated no significant difference in the effectiveness of attitude change. This outcome was attributed to the short duration of the educational intervention, which needed to be increased to induce immediate changes in attitudes. Implications: The study suggests the necessity for age-appropriate and sustainable sexual education through counseling or engaging media provided by schools to ensure long-term effectiveness in changing students' attitudes.